UNDERSTANDING TRUCK OVERLOADING BEHAVIOUR AND ITS CONTROL: A REVIEW OF PREVIOUS STUDIES - IGW Samsi Gunarta (Jurnal Jalan-Jembatan, 2007)
Overload offences have not been a problem if developing countries. Various countries as well, even in the USA. However, the solutions taken have not considered the background of overload offences but tended to be pragmatic and neglected the main problem. The paper is a preliminary study of overload offences taken from some countries experiences. Study reveals that the solution has been focused on infrastructure providers side rather than dealing with the problem comprehensively. Various gaps found in the research mainly factors related tooverloading behaviour. Keywords : Overloading, Freight Transport, Load Enforcement, Loading Impact,